READING PASSAGE IN ENGLISH TEXTBOOK FOR SMP ISSUED BY DEPARTMENT OF EDUCATION & CULTURE SAMARINDA - Iwan Setiawan (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2016)
This study aimed to describe characteristics of reading passages in the English textbook for SMP in Samarinda published by CV Nadia Sarana Utama.  The study used content analysis as the design.  The data of this study were 11 reading passages in the English textbook.  The reading passages were evaluated based on topic, organization, grammatical features, cohesion and cohesive devices of the text, and vocabulary choices.  The study revealed that the topics of the reading text were not clear.  Of 11 passages available, 3 do not have topic, 2 do not state relevant topic, and 6 has relevant topic.  Cohesion and cohesive of the texts were achieved by reference and the conjunction (text 1 to text 11), substitution (texts 4, 6, and 10) and lexical cohesion (texts 4, 7, and 10). Grammatical features of the 11 texts are simple and compound sentence. Vocabulary texts are everyday language.